2021
DOI: 10.1002/ehf2.13703
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP as a marker for atrial fibrillation and heart failure in four observational outpatient trials

Abstract: Aims Heart failure (HF) and atrial fibrillation (AF) frequently coexist and are both associated with increased levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). It is known that AF impairs the diagnostic accuracy of NT‐proBNP for HF. The aim of the present study was to compare the diagnostic and predictive accuracy of NT‐proBNP for HF and AF in stable outpatients with cardiovascular risk factors. Methods and results Data were obtained from the DIAST‐CHF trial, a prospective cohort study that rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…As such, there may be some misclassification in documented outcomes prior to 2005. Lastly, our analysis did not account for cardiac conditions such as atrial fibrillation or valvular heart disease, which may impact levels of NT-proBNP . Future analysis on the relationship between NT-proBNP, atrial fibrillation and HF is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there may be some misclassification in documented outcomes prior to 2005. Lastly, our analysis did not account for cardiac conditions such as atrial fibrillation or valvular heart disease, which may impact levels of NT-proBNP . Future analysis on the relationship between NT-proBNP, atrial fibrillation and HF is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of AF and HFpEF is often underestimated in clinical practice, presumably because unrecognized AF occurs years before patients receive a diagnosis, and patients suffer from exertional dyspnea before physicians detect the presence of heart failure. The diagnosis of HFpEF on the basis of natriuretic peptides is very limited or even impossible in AF patients with suspected HFpEF [ 44 ].…”
Section: Comorbidities: Prevalence Impact On Prognosis Treatment Optionsmentioning
confidence: 99%
“…There is serious concern about the strict resemblance of NP predictive values among patients with HFrEF/HFmrEF to those with HFpEF [37]. The DIAST-CHF trial revealed that NT-proBNP was a better predictor of incident atrial fibrillation than HF among stable outpatients with CV risk factors [38]. Importantly, clinical use of NPs has a well-established economic benefit when compared with other cardiac and non-cardiac biomarkers.…”
Section: Biomarkers Of Myocardial Stretch and Biomechanical Stressmentioning
confidence: 99%